Determinants Of Oral corticosteroid Responsiveness in Wheezing Asthmatic Youth (DOORWAY): protocol for a prospective multicentre cohort study of children with acute moderate-to-severe asthma exacerbations. Issue 4 (7th April 2014) - Ducharme, F M; Zemek, R; Gravel, J; Chalut, D; Poonai, N; Laberge, S; Quach, C; Krajinovic, M; Guimont, C; Lemière, C; Guertin, M C
Abstract : Introduction: Oral corticosteroids are the cornerstone of acute asthma management in the emergency department. Recent evidence has raised doubts about the efficacy of this treatment in preschool-aged children with viral-induced wheezing and in smoking adults. The aims of the study were to: (1) document the magnitude of response to oral corticosteroids in children presenting to the emergency department with moderate or severe asthma; (2) quantify potential determinants of response to corticosteroids and (3) explore the role of gene polymorphisms associated with the responsiveness to corticosteroids. Methods and analysis: The design is a prospective cohort study of 1008 children aged 1–17 years meeting a strict definition of asthma and presenting with a clinical score of ≥4 on the validated Pediatric Respiratory Assessment Measure. All children will receive standardised severity-specific treatment with prednisone/prednisolone and cointerventions (salbutamol with/without ipratropium bromide). Determinants, namely viral aetiology, environmental tobacco smoke and single nucleotide polymorphism, will be objectively documented. The primary efficacy endpoint is the failure of emergency department (ED) management within 72 h of the ED visit. Secondary endpoints include other measures of asthma severity and time to recovery within 7 days of the index visit. The study has 80% power for detecting a risk difference of 7.5% associated with each determinant from a baseline risk of 21%, at an α of 0.05. Ethics and dissemination: Ethical approval has been obtained from all participating institutions. An impaired response to systemic steroids in certain subgroups will challenge the current standard of practice and call for the immediate search for better approaches. A potential host–environment interaction will broaden our understanding of corticosteroid responsiveness in children. Documentation of similar effectiveness of corticosteroids across determinants will provide the needed reassurance regarding current treatment recommendations. Results: Results will be disseminated at international conferences and manuscripts targeted at emergency physicians, paediatricians, geneticists and respirologists. Trial registration number: This study is registered at Clinicaltrials.gov (NCT02013076 ).